Elder self-neglect: A discussion of a social typology - Paveza, Gregory; Weerd, Carla Vande; Laumann, Edward (Journal of the American Geriatrics Society, 2008)
This article presents a theoretical framework for the study of social and behavioral factors associated with elder self-neglect. The model presented reflects the authors' beliefs that a risk-vulnerability model offers a useful framework from which to study all forms of elder mistreatment, as well as elder self-neglect. This model has particular utility, because it can begin to define the elements of risk and vulnerability that may be addressed using preventative measures as opposed to solely addressing intervention, which is often the case when addressing elder mistreatment and self-neglect. The authors then address a method for using the Consortium for Research in Elder Self-neglect of Texas data as currently constructed and adding to that database to effectively study risks and vulnerabilities in the elder self-neglect population. These additional data would greatly expand the scope of the study. The discussant adds his perspective to the ideas proposed by the authors.
21 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000261064700007
Keywords: Aged; Alzheimer disease; Elder Abuse; Elderly; Geriatric Assessment; Humans; Risk Adjustment; Self-neglect; Social Behavior; Social networks; caregiver burden; cognitive defect; conceptual framework; conference paper; daily life activity; data base; depression; dept.hhs; family violence; functional disease; gerontological research; home environment; human; mental disease; peer-reviewed; preventive health service; self neglect; social aspect; social psychology; social support; substance abuse

Assessment of the elderly - Paveza, Gregory (Comprehensive Handbook of Social Work and Social Welfare, 2008)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs